Evaluation of modified Killian's method: A technique to expose the hypopharyngeal space. (10th June 2014) - Murono, Shigeyuki; Tsuji, Akira; Endo, Kazuhira; Kondo, Satoru; Wakisaka, Naohiro; Yoshizaki, Tomokazu
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The objective of this study was to evaluate the "Modified Killian's method, " a recently proposed endoscopic technique to observe a wider area of the hypopharngeal space than is possible with the conventional method. Study Design Prospective case series. Methods Fifty‐seven patients underwent transnasal flexible endoscopy in a sequence of eight different procedures with or without head torsion, the Valsalva maneuver, and a position similar to bowing named "the modified Killian position." The visibility of subsites of the hypopharynx and esophageal inlet was evaluated based on a 5‐point scale. Results The Modified Killian's method, a combination of all three procedures of head torsion, the Valsalva maneuver, and the modified Killian position, demonstrated a highly significant score for hypopharyngeal visibility. Previous treatment with radiotherapy or chemoradiotherapy did not significantly affect the visibility of the hypopharynx. Conclusion The newly proposed Modified Killian's method provides an effective view of the entire circumference of the hypopharyngeal space even in patients receiving radiotherapy. This useful procedure can be performed easily and should be a part of flexible laryngoscopy for outpatients. Level of Evidence 4. Laryngoscope, 124:2526–2530, 2014